Cross-Reactivity of IgG Antibodies and Virus Neutralization in mRNA-Vaccinated People Against Wild-Type SARS-CoV-2 and the Five Most Common SARS-CoV-2 Variants of Concern - Schwarze, Mandy; Krizsan, Andor; Brakel, Alexandra; Pohl, Fabian; Volke, Daniela; Hoffmann, Ralf (Frontiers in Immunology, 2022)
The rapid development, approval, and production of vaccines against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in less than 1 year after the first reports of a new infectious disease was a real game changer, providing 80%–90% efficacy in preventing severe etiopathologies of the coronavirus disease 2019 (COVID-19). These vaccines induce an immune response against the SARS-CoV-2 spike (S) protein located on the surface of the virus particle. Antibodies (Abs) recognizing the S-protein can inhibit binding of the virus via the S-protein to the angiotensin-converting enzyme-2 (ACE-2) receptor expressed on different human cells, especially when these Abs bind to the interaction site, the so-called receptor-binding domain (RBD). We have expressed the RBDs of wild-type SARS-CoV-2 and five variants of concern (VOCs) to test the immune response in people before vaccination with mRNA vaccines BNT162b2 and mRNA-1273 and after up to three vaccinations using in-house ELISA and inhibition assays. The methods of both assays are provided. Both vaccines initiated similarly high IgG titers after two vaccinations against the wild-type and even two VOC-RBDs (alpha and delta) and strongly inhibited the corresponding RBD-ACE-2 binding. The IgG titers and inhibition of ACE-2 binding were lower for beta and gamma RBDs and much lower for omicron RBD. The third vaccination after 6 months strongly increased both the IgG titers and the neutralizing effect against all variants, especially for omicron, leading to 63% ± 13% neutralization potential. Importantly, neutralization linearly increased with the IgG titers.